Effect of Carbon Monoxide on Active Oxygen Metabolism of Postharvest Jujube - Zhang, Shaoying; Li, Qin; Mao, Yulan (Journal of Food Technology Research, 2014)
To prolong the shelf life postharvest jujube, the effect of carbon monoxide (CO) on senescence of postharvest jujube in relation to active oxygen metabolism was investigated. Jujubes were fumigated with CO gas at 5, 10, 20 or 40μmol/L for 1 h, and then stored for 30 days at room temperature. Changes in membrane permeability, malonaldehyde (MDA), H2O2, O2•− content, and activities of active oxygen metabolism associated enzymes including superoxide dismutase (SOD), catalase (CAT) and peroxidase (POD) in fruit were measured. The results indicated that a little of CO could exhibit positive physiological effect on controlling senescence of winter jujube during storage. The study further showed that fumigating jujube fruit with 10 μmol/L CO could reduce increase of MDA content and the relative membrane permeability, effectively inhibit oxidative damage to lipids, decrease H2O2 and O2•− content and maintain high activities of SOD, CAT and POD. The present data suggest that exogenous CO treatment might delay the jujube fruit senescence by regulating active oxygen metabolism.